2016
DOI: 10.1007/s10787-016-0288-x
|View full text |Cite
|
Sign up to set email alerts
|

TRP channels: potential drug target for neuropathic pain

Abstract: Neuropathic pain is a debilitating disease which affects central as well as peripheral nervous system. Transient receptor potential (TRP) channels are ligand-gated ion channels that detect physical and chemical stimuli and promote painful sensations via nociceptor activation. TRP channels have physiological role in the mechanisms controlling several physiological responses like temperature and mechanical sensations, response to painful stimuli, taste, and pheromones. TRP channel family involves six different T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 129 publications
0
46
0
1
Order By: Relevance
“…Interestingly, CBDA also targets the TRP family of ion channels (De Petrocellis et al, ), including TRPV1 (Ligresti et al, ). TRP channels detect physical and chemical stimuli and promote painful sensations via nociceptor activation (Marwaha et al, ) and the stimulating effects of cannabinoids at TRPV1 may lead to desensitization of this channel (Morita et al, ; Ursu, Knopp, Beattie, Liu, & Sher, ). Furthermore, CBDA has been shown, by computational modelling and cell culture‐based experiments, to act as a dual PPAR‐α and PPAR‐γ agonist (D'Aniello et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, CBDA also targets the TRP family of ion channels (De Petrocellis et al, ), including TRPV1 (Ligresti et al, ). TRP channels detect physical and chemical stimuli and promote painful sensations via nociceptor activation (Marwaha et al, ) and the stimulating effects of cannabinoids at TRPV1 may lead to desensitization of this channel (Morita et al, ; Ursu, Knopp, Beattie, Liu, & Sher, ). Furthermore, CBDA has been shown, by computational modelling and cell culture‐based experiments, to act as a dual PPAR‐α and PPAR‐γ agonist (D'Aniello et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Blocking the activity of the channel by the administration of TRPM8 antagonists or by genetic ablation using mice lacking TRPM8, significantly attenuated thermal responses in nerve injury‐induced pain (Knowlton et al, ; Patel et al, ). This evidence suggests that the in vivo antagonism of TRPM8 holds promise for the successful treatment of neuropathic cold hypersensitivity (Marwaha et al, ; Weyer and Letho, ). A key challenge in the discovery of TRPM8 blockers is the identification of highly selective molecules with a good pharmacokinetic profile suitable to provide an efficacious dose response.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, it is widely expressed on terminals of thermosensitive neurons that innervate peripheral tissues including the skin, tongue, teeth and cornea (Abe et al, ; Parra et al, ). Several studies in animals and humans have clearly demonstrated the role of TRPM8 in pain perception (Marwaha et al, ); nevertheless, its precise role in pain modulation remains a matter of debate (Namer et al, ; Proudfoot et al, ). Application of relatively low doses of menthol (TRPM8 agonist) is associated with a cooling sensation and even pain relief, while at higher doses, the same drug causes burning, irritation and pain (Wasner et al, ; Hatem et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Mammalian TRP channels have not only oral location, but a broad tissue distribution (at least one type of TRP present virtually in all cells), this ubiquity bringing them to the vanguards of the chemosensorial system [132, 347, 348]. …”
Section: Energetic Nature (Virya) Mediated By Trpsmentioning
confidence: 99%